FORMULATION OF CHITOSAN TRIPOLYPHOSPHATE-TETRANDRINE BEADS USING IONIC GELATION METHOD: IN VITRO AND IN VIVO EVALUATION - Iswandana, Raditya; Putri, Kurnia Sari Setio; Dwiputra, Randika; Yanuari, Tryas; Sari, Santi Purna; Djajadisastra, Joshita (International Journal of Applied Pharmaceutics, 2017)
Objective: Drug delivery to the colon via oral route can be directly treated a variety of diseases in the colon, such as fibrosis. Tetrandrine is a drug that has anti-fibrosis effects. In this study, chitosan-tripolyphosphate (TPP) beads containing tetrandrine was made and evaluated for in vitro release profile and in vivo targeted test. Methods: Chitosan-TPP tetrandrine beads were prepared by ionic gelation method with variation in sodium tripolyphosphate concentration: 3% (Formula 1), 4% (Formula 2), and 5% (Formula 3). All formulae were characterized for its morphology, particle size, moisture content, process efficiency, entrapment efficiency, thermal character, crystallinity, and swelling. Then, the best formula was coated with HPMCP HP-55, CAP, Eudragit L100-55, or Eudragit L100 prior to drug release profile in vitro and in vivo test. Results: Beads from all formulae had an average size: 920.50±0.04 µm, 942.21±0.08 µm, and 1085.95±0.03 µm; Water content: 7.28±0.003%, 5.64±0.005%, and 6.84±0.004%; Process efficiency: 29.70%, 28.96%, and 29.70%; Entrapment efficiency: 16.20±0.63%, 17.02±0.37%, and 20.42±0.70% for Formula 1, 2, and 3, respectively. In addition, the results of in vitro cumulative drug release were 67.36%, 76.04%, 83.12%, 83.21%, 40.16%, 37.98%, 45.86%, 41.71% for Formula 3A-3H, respectively. Conclusion: It can be concluded that Formula 3D (CAP 15%) was chosen as a formulation with the best in vitro profile. Moreover, the in vivo targeted test showed that Formula 3D was able to deliver the beads to the intestine compared to the control beads.